The interval Shapley value of an M/M/1 service system - E, Cheng-Guo; Li, Quan-Lin; Li, Shiyong (Zielona Góra: Uniwersytet Zielonogórski)
Service systems and their cooperation are one of the most important and hot topics in management and information sciences. To design a reasonable allocation mechanism of service systems is the key issue in the cooperation of service systems. In this paper, we systematically introduce the interval Shapley value as cost allocation of cooperative interval games (N, V) arising from cooperation in a multi-server service system, and provide an explicit expression for the interval Shapley value of cooperative interval games (N, V).
Keywords: M/M/1 service system; cooperative interval game; cost allocation; Shapley value